Status Fitonematoda pada Tiga Kisaran Umur Lahan Pertanaman Pisang Cavendish di Way Kambas, Lampung - Yanto Yanto; I Gede Swibawa (Jurnal Fitopatologi Indonesia, 2016)
Crop losses due to phytonematodes infection commonly occurred on intensive plantation practiced for a long time. The research was aimed to study phytonematodes status on several age-different plantation of Cavendish banana in PT NTF Way Kambas, Lampung. Soil and root samples were taken from three different plantations, selected based on time period of cultivation practice, i.e. 3–5, 10–12, and 17–19 years long. The modification of Baermann funnel method was applied to collect nematodes. The status of phytonematodes were determined based on the absolute frequency (AF), relative frequency (RF), and absolute population (AP) of each genus. The results showed that 13 phytonematodes genera inhabited Cavendish banana crops. Pratylenchus and Radopholus have important status on a land that had been cultivated for 3–5 and 10–12 years with AF 100%, RF 31%, and  AP 298.8, and 423.0  individues per 200 mL of soil, respectively on 3–5 years long lands, and AF100%, RF 39% and PA 215, and 126 individues per 200 mL of soil, respectively on 10–12 years long lands. Pratylenchus and Radopholus were less important on 17–19 years long rotated lands with AF 77%, RF 22% and AP 33.0 and 16.4 individues per 200 mL of soil respectively. The status of other phytonematodes were not important with low value of AF, RF, and AP.